Risk factors of household transmission of pandemic (H1N1) 2009 among patients treated with antivirals: a prospective study at a primary clinic in Japan. - Nobuo Hirotsu (Public Library of Science (PLoS), 2012)
Background Household transmission of influenza can affect the daily lives of patients and their families and be a trigger for community transmission, thus it is necessary to take precautions to prevent household transmission. We aimed to determine the risks of household transmission of pandemic (H1N1) 2009 influenza virus from an index patient who visited a primary clinic and was treated with antiviral drugs. Methods We followed up all the patients who were diagnosed with influenza A by rapid diagnostic test with a questionnaire or interview from July 2009 to April 2010. Secondary cases were defined as patients visiting the clinic or other clinics and being positive for influenza A by rapid diagnostic test within 7 days of onset of an index patient. Logistic regression analysis was used to explore the association between household transmission and the studied variables. Results We recruited 591 index patients and 1629 household contacts. The crude secondary attack rate was 7.3% [95% confidence interval (CI): 6.1-8.7]. Age of index patients (0-6 years old: odds ratio 2.56; 95% CI: 1.31-4.01; 7-12 years old: 2.44, 1.31-3.72; 30-39 years old 3.88; 2.09-5.21; 40 years old or more 2.76; 1.17-4.53) and number of household members with five or more (3.09, 2.11-4.07), medication started ≥48 hours from the onset of fever (2.38, 1.17-3.87) were significantly associated with household transmission. Conclusions Household transmission was associated with index patients aged ≤12 years old and adults ≥30 years with children, with more than five persons in the household, and medication initiated ≥48 hours from the onset of fever among the population, in which, antiviral treatment was given to all patients. We need to warn patients at high risk of household transmission to take additional precautions.